Investigation of Secondary School, Undergraduate, and Graduate Learners' Mental Models of Ionic Bonding. - Coll, R.; Treagust, David (Wiley Periodicals, 2003)
Secondary school, undergraduate, and graduate level learners' mental models of bonding in ionic substances were explored using an interview protocol that involved the use of physical substances and a focus card containing depictions of ionic bonding and structure. Teachers and faculty from the teaching institutions were interviewed to contextualize teaching models within the educational setting for the inquiry. These data resulted in two socially negotiated consensus teaching models and a series of criterial attributes for these models: the essential qualities, all of which must be negotiated, if the model is used in a way that is acceptable to scientists. The secondary school learners see ionic bonding as consisting of attraction of oppositely charged species that arise from the transfer of electrons driven by the desire of atoms to obtain an octet of electrons. The undergraduates see the lattice structure as a key component of ionic substances and quickly identified specific ionic lattices for the physical prompts used as probes. The graduates also identified strongly with ionic lattices, were less likely to focus on particular ionic structures, and had a stronger appreciation for the notion of the ionic-covalent continuum. The research findings suggest that learners at all educational levels harbor a number of alternative conceptions and prefer to use simple mental models. These findings suggest that teachers and university faculty need to provide stronger links between the detailed nature of a model and its intended purpose.